Potret Fasilitas Perkotaan Di Indonesia Timur/Barat: Studi Perbandingan Kota Surabaya Dan Kota Palu - Dwison, Yunde Almoora; Dudung, Jiniar; Ahmad, Satrio; Arya, Moh.; Risqullah, Ramadhan Afdal; Rachmad (JPS: Journal of Publicness Studies, 2026)
This study aims to analyze the differences in the average development of technology, information, and infrastructure in eastern/western Indonesia and focuses on the comparison between the western and eastern regions of Indonesia in the context of Indonesia as an archipelagic country, infrastructure is very important to create interconnectivity between islands in Indonesia. This study uses a qualitative approach with a descriptive-comparative method. Data were obtained through in-depth interviews, field observations, and documentation studies of regional development policies and planning. This study focuses on an in-depth understanding of the condition of facilities and infrastructure in the cities of Surabaya and Palu. The results of this study are compiled based on a comparative analysis of the quality of the condition of facilities and infrastructure (sapras) in the cities of Surabaya and Palu. Comparative findings show quite striking differences between the two regions, which are inseparable from the historical background of city development, the function and strategic role of the region, the socio-economic conditions of the community, as well as the characteristics and geographical challenges faced by each region. In terms of urban facilities in the city of Surabaya is relatively more complete, integrated, and sustainable compared to the city of Palu. These differences are influenced by factors such as regional fiscal capacity, the level of urbanization, historical experience of development, and the impact of natural disasters experienced by the city of Palu. This research is expected to provide academic and practical contributions to the development of more equitable urban development policies across regions.